WORK AND LEISURE: A CORRELATIONAL INVESTIGATION - Cobrador, Fatima R.; Vasquez, Michael B.; Begas, Samson (IDEAS: Journal of Management & Technology, 2024)
The complex relationship between work and leisure is imperative for fostering a comprehensive approach to enhancing individual’s overall quality of life. This study investigated the extent of work aspect and degree of leisure of 223 elementary school teachers in the District of Dumarao, with a specific focus on elements such as physical environment, psychological, technological, passive leisure and active leisure of teachers. The study placed emphasis on the critical need to understand the relationship between work and leisure. The study examined the extent of work aspect and the degree of leisure in the District of Dumarao, exploring potential variations based on teachers' age, sex, highest educational attainment and length of service.  The study focus to quantify the amount of time spend on work related tasks and leisure activities, shed light on the challenges and opportunities for improving the well-being and job satisfaction of teachers.  It identified a gap in understanding how teachers in the Philippines, specifically in Capiz, manage their professional and personal lives. The study utilized a quantitative descriptive correlational research design in which data were collected through a questionnaire and analyzed using IBM SPSS Statistics version 26, employing various statistical methods such as frequency, mean, t-test, f-test, and Pearson’s correlation. The finding revealed that the extent of work was very high and the degree of leisure was high among elementary school teachers with no significant difference based on sex, age, highest educational attainment, and length of service with significant relationship between the extent of work and the degree of leisure of elementary school teachers. The study emphasized the relationship between work and leisure, in response to the heightened desire for leisure among teachers facing increased workloads, school administrators may consider implementing stress management and wellness program by providing resources and support for teachers to cope with stress can positively impact their overall job satisfaction and well-being.